Weed Management in Wheat by Cuscuta Alone and in Combination with Commercial Weedicides Allymax and Axial - ABDULLAH,Y. (2020)
ABSTRACT: The present study was to assess the additive effects of cuscuta (akasbel) aqueous extract alone and in combination with full and reduced doses of commercially available weedicides against weeds in wheat crop during the year 2016-2017. The study was conducted in a randomized complete block design (RCBD) with 3 replications. The results showed that hand weeding and use of weedicides Allymax and Axial (full and half recommended doses) significantly controlled all prevailing weeds and increased yield and yield contributing parameters over the weedy check/control and sole application of cuscuta aqueous extract. Hand weeding and Allymax (full dose) showed minimum weed population, relative density, fresh and dry weed biomass and higher leaf area index (LAI), leaf area duration (LAD), crop growth rate (CGR), plant height, 1000 grain weight and grain yield while net assimilation rate (NAR), chlorophyll content, number of tillers, spike length, grains spike-1 and biological yield were maximum only in hand weeding. These findings suggest that in order to attain highest wheat yield, the field should be kept free from weeds by hand weeding (if labour is not a limiting factor) or use recommended dose of weedicide Allymax for efficient weed management in wheat.